PROGRAM PENGENALAN DIRI DAN PASANGAN UNTUK MENINGKATKAN KESIAPAN PERNIKAHAN PADA PASANGAN PRANIKAH - , PRISCILIA THEA NOVENA; , Dra. Kwartarini W.Y., M.Med., Sc., Ph.D., Psi. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
ThebackgroundofthisstudyistheresearcherâsexperiencewhendoingapprenticeinCommunityHealthCenterinMoyudan,Slemandistrict.Thepracticeofpremaritalcounselingwaslessoptimum,besidesthatmanypremaritalcouplesdidnotfeelreadyinfacingmarriagelife,forexample:feelinganxious,fearandconfusedindealingwiththeirstatuschanging.Basedonthatphenomenon,itisconsiderednecessarytohaveSelfandPartnerRecognitionProgramwhichcanbeappliedbypsychologistsingivingpreparationforpremaritalcopletoimprovetheirunderstandingsandskillsaboutcomplexityinmarriagelife.ThepurposeofthisresearchistoknowthesignificanceofSelfandPartnerRecognitionProgramonthepremaritalcouplesâreadinesstogetmarried.Theparticipantsinthisresearchweretenpremaritalcouplesthatweredividedintoanexperimentgroupandacontrolgroup(waitinglist).Themeasurementusedinthisresearchwasreadinessmaritalscalewhichwasgivenbefore,afterandaweekfollow-upafterprogramdeliverance.Theresultofthisresearchwasanalyzedbothquantitativelyandquantitatively.TheresultshowedthatSelfandPartnerRecognitionProgramcouldimprovesignificantlythemarriagereadinessofpremaritalcouple,withscoreZ